Report on Italy Earthquake (24th August 2016) - Taranjot Singh (Journal of Civil Engineering and Environmental Sciences - Peertechz Publications, 2017)
On 24 August 2016, a magnitude of 6.2 earthquake hit the Apennines Mountains in central Italy, devastating the small towns of Amartrice, Accumoli and Pescare del Tronto. At least 293 lives were lost. This is the latest in a series of heavy earthquakes to hit Italy in recent years. The country is particularly exposed to earthquakes risk as it is located where continental plates collide and building stock is vulnerable. Yet just over 1% of residential buildings are insured against earthquakes. How can Italy and its residents better prepare for future events?